Connection provisioning with feasible shareability determination for availability-aware design of optical networks - Kantarci, Burak; Mouftah, Hussein T.; Oktug, Sema (IEEE, 2008)
In this paper, we present two adaptive connection provisioning algorithms to offer better availability per connection under dynamic traffic with shared backup path protection. The proposed schemes monitor the status of the network in terms of resource consumption and average unavailability per connection and adapt the sharing degree for the links. We compare our heuristic and optimized sharing degree approach with a conventional connection provisioning approach under two different topologies. The simulation results show that our proposed approaches offer better availability to incoming connection requests. Results referring to resource overbuild guarantee that shared backup protection is not violated since resource overbuild is kept in a feasible range.